2012
DOI: 10.1037/a0026699
|View full text |Cite|
|
Sign up to set email alerts
|

Intelligence: New findings and theoretical developments.

Abstract: We review new findings and new theoretical developments in the field of intelligence. New findings include the following: (a) Heritability of IQ varies significantly by social class. (b) Almost no genetic polymorphisms have been discovered that are consistently associated with variation in IQ in the normal range. (c) Much has been learned about the biological underpinnings of intelligence. (d) "Crystallized" and "fluid" IQ are quite different aspects of intelligence at both the behavioral and biological levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

32
584
2
40

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 792 publications
(658 citation statements)
references
References 311 publications
(299 reference statements)
32
584
2
40
Order By: Relevance
“…In conjunction with the expanding literature that shows associations between general cognitive ability and a wide range of physical health variables including mortality (Deary, Weiss, & Batty, 2010), this suggests that cognitive ability may account for (confound) some of the associations between health literacy and actual health outcomes. If cognitive ability in general, and not Understanding health literacy and health 5 just skills and knowledge specific to health is consequential for health, then plans to improve health by increasing health literacy (Baur & Ostrove, 2011) may be informed by the attempts to raise general cognitive ability (Nisbett et al, 2012). Likewise, prevention and health services could be adjusted to meet people's cognitive skills in a broader set of areas, not just literacy or numeracy alone.…”
Section: And the Test Of Functional Health Literacy Inmentioning
confidence: 99%
“…In conjunction with the expanding literature that shows associations between general cognitive ability and a wide range of physical health variables including mortality (Deary, Weiss, & Batty, 2010), this suggests that cognitive ability may account for (confound) some of the associations between health literacy and actual health outcomes. If cognitive ability in general, and not Understanding health literacy and health 5 just skills and knowledge specific to health is consequential for health, then plans to improve health by increasing health literacy (Baur & Ostrove, 2011) may be informed by the attempts to raise general cognitive ability (Nisbett et al, 2012). Likewise, prevention and health services could be adjusted to meet people's cognitive skills in a broader set of areas, not just literacy or numeracy alone.…”
Section: And the Test Of Functional Health Literacy Inmentioning
confidence: 99%
“…According to this study, the effect of prolonged educational process in adolescence on intelligence is significant at the age of 19 years [11]. It was also found that students who miss one year of schooling in the future show slightly lower results on intelligence tests [9]. Poor performance on intelligence tests in a number of studies was also associated with long summer holidays, when there is no systematic educational impact [9].…”
Section: Introductionmentioning
confidence: 97%
“…Several papers showed that these factors contribute significantly to the individual differences in non-verbal intelligence [3,9]. Crosscultural differences are explained often by differences in features like thinking, for example, in East Asian (holistic thinking) and western (analytical thinking) cultures [9], differences in the structure of the language, such as Chinese characters and the Russian alphabet (e.g., [10]), and the type of cultural communities (ratio of the scales 'collectivism -individualism' and 'independenceinterdependence'). In particular, a significant positive effect of education on individual differences in intelligence was found in the Norwegian natural experiment, when as a result of the reform of public education two additional years of study after the seventh grade were introduced [11].…”
Section: Introductionmentioning
confidence: 99%
“…Although there is a certain amount of fluctuation in these estimates for various indicators of fluid reasoning and crystallized knowledge, with the latter being more heritable than the former (Kan et al 2013), the field has converged, after a number of meta-analyses, on the estimate of 0.5 for general cognitive ability, which is a higherorder index derived from both fluid and crystallized capacities (Plomin et al 2013a). Although there is not unanimous enthusiasm regarding the value of heritability and familiality studies to the field (Charney 2012;Nisbett et al 2012;Richardson 2013), there is still a massive related research effort to further differentiate and stratify the obtained estimates throughout the life span (e.g., Haworth et al 2010;van Soelen et al 2011) and in the context of different moderators (e.g., Molenaar et al 2013). Yet, the epicenter of the related research has moved away from the question of whether the genome influences cognitive abilities to the question of how it actually exerts this influence.…”
Section: Involved In Critical-analytic Thinkingmentioning
confidence: 99%